Smart mailbox with security system / Muhammad Eizaz Afzal Mohamad Zamree ... [et al.] - Mohamad Zamree, Muhammad Eizaz Afzal; Yusni, Muhammad Afif Sufi; Mohmmad Najib, Muhammad Luqman Hakim; Hamdan, Muhammad Nafis; Suhaimi, Muhammad Shakir Zufayri; Song, Saw-Imm (Universiti Teknologi MARA, Perak, 2020)
The limitation on the usage of traditional mailboxes is that the recipients are not always at home to receive the parcels and confirm the delivery. Sometimes the undelivered consignments remain stored at the post office or other contact delivery point which cause great inconveniences to the receivers. In addition, the current mailboxes have less security features that it may have a high probability of missing. This project focuses on improving the current mailbox functions so that it can help the receivers and courier services to have a more secure and efficient parcel receiving system. This product consists of a Smart IOT Technology system, camera and servomotor that will provide a secure system for the users. The servomotor will be used to lock or open the door of the smart mailbox through mobile phone by using a Blynk application. The camera acts as a monitoring system and can be accessed by the receivers through their mobile phones. The mailbox has a push button that allows the courier service man to push and send the notification to the receiver, so that the receiver can open the lock of SMIX and allow the delivery man to safely put the parcels inside the smart mailbox.